2022
DOI: 10.21203/rs.3.rs-2046019/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimum Location of Shear Wall in G+6 Building at the Outer Periphery Using Pushover Analysis

Abstract: Many studies have been conducted in recent years to determine how well buildings handle lateral forces. However, the location of the shear wall when a building is subjected to lateral force was not thoroughly studied. It is well known that performance-based design is the best method for determining the ideal location. Pushover analysis is used to find the best location for this study. When conducting a pushover analysis, the relationship between base shear and roof displacement is typically depicted in the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Optimizing the design through shear wall locations and configurations upon obtaining a minimal cost with maximum performance was also studied by researchers. A pushover analysis was performed by [11] to find the optimum location of shear walls in a seven-story building. It was found that the model with shear walls positioned along the four edges, pushw6, is the optimum position for the shear walls.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the design through shear wall locations and configurations upon obtaining a minimal cost with maximum performance was also studied by researchers. A pushover analysis was performed by [11] to find the optimum location of shear walls in a seven-story building. It was found that the model with shear walls positioned along the four edges, pushw6, is the optimum position for the shear walls.…”
Section: Introductionmentioning
confidence: 99%